2022
DOI: 10.3389/fenvs.2022.963549
|View full text |Cite
|
Sign up to set email alerts
|

Promoting sustainable entrepreneurship in training and education: The role of entrepreneurial culture

Abstract: The main purpose of this research was to investigate how universities may help Saudi Arabian students who are planning to become entrepreneurs promote sustainability development goals. The intersection of ecological development and entrepreneurship is referred to as “sustainable entrepreneurship.” Entrepreneurs want to provide practical educational solutions. Thus, this study seeks to fill this gap by developing a new model for measuring the relationships between entrepreneurial culture, sustainability trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…In the Gulf region, the university's entrepreneurial education and the transformation of universities towards entrepreneurship have been argued to encourage entrepreneurial success and regional innovation processes (Hashimi et al, 2021;Shahwan and Zaman, 2023;Varadarajan Sowmya et al, 2010). However, promoting an entrepreneurial culture in the Gulf region is a societal task that require long-term education and a change of economic incentives (Jabeen et al, 2017;Zahrani, 2022). Universities themselves need to reflect this culture and take risks through increased collaboration with industries (Bhayani, 2015).…”
Section: Being Youmentioning
confidence: 99%
“…In the Gulf region, the university's entrepreneurial education and the transformation of universities towards entrepreneurship have been argued to encourage entrepreneurial success and regional innovation processes (Hashimi et al, 2021;Shahwan and Zaman, 2023;Varadarajan Sowmya et al, 2010). However, promoting an entrepreneurial culture in the Gulf region is a societal task that require long-term education and a change of economic incentives (Jabeen et al, 2017;Zahrani, 2022). Universities themselves need to reflect this culture and take risks through increased collaboration with industries (Bhayani, 2015).…”
Section: Being Youmentioning
confidence: 99%
“…Despite the growing emphasis on sustainability in Saudi Arabia (Alotaibi, 2021;Zahrani, 2022), there still exists a significant research gap in the literature on sustainability practices and student academic achievement in Saudi Arabia's unique educational environment. The government focuses more on sustainability, but psychological empowerment and the digital learning environment are rarely examined as mediating or moderating elements.…”
Section: Background Of Studymentioning
confidence: 99%
“…Higher education plays a significant role in educating future change agents (Zhou et al, 2020). More specifically, entrepreneurship education is highlighted as a crucial component of education for sustainable development (Zahrani, 2022). Several entrepreneurship education approaches have enabled universities to educate change agents in all disciplines (Aadland & Aaboen, 2020;Neergård et al, 2022), as evidenced by a recent study that revealed five distinct profiles among business students based on their sustainable and entrepreneurial attitudes, highlighting the need for targeted educational strategies that address the varied entrepreneurial intentions within these groups to effectively foster sustainable business practices (Jebsen et al, 2023).…”
mentioning
confidence: 99%